19.FEEDBACK FROM FINAL-YEAR STUDENTS ABOUT THE TRAINING PROGRAM FOR PREVENTIVE MEDICINE DOCTORS FROM 2020 TO 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the feedback of final-year students about the Preventive Medicine Doctor training program from 2020 to 2023.Research method: A cross-sectional study of 333 final-year Preventive Medicine Doctor students at Hanoi Medical University, course 2014-2020; course 2015-2021; course 2016-2022; course 2017-2023. Use pre-designed questions sent to classes for students to fill out themselves.Results: Regarding the program objectives, the percentage of students who agreed and strongly agreed was 53,5% and 27,3%, respectively. Regarding the organization of teaching activities, the percentage of students who agreed and strongly agreed was 58,6% and 20,7%, respectively. Regarding the knowledge outcome standards, the percentage of students who felt confident and very confident was 41,4% and 1,5%, respectively. Regarding the skill outcome standards, the percentage of students who felt confident and very confident was 57,1% and 13,2%, respectively. Females have an odds ratio of 1.68 times higher than males regarding the positive response rate to the knowledge outcome standard (OR = 1.68; CI = 1.04–2.72). Regarding factors related to the positive response rate to the skills outcome standard, students with Good/Excellent academic performance have an odds ratio of 0.42 times lower than students with Average/Fair academic performance (OR = 0.42; 95% CI = 0.26–0.68), and students living in urban areas have an odds ratio of 0.49 times lower than those in rural areas (OR = 0.49; 95% CI = 0.28–0.82). These differences are statistically significant with p < 0.05.Conclusion: Preventive Medicine students responded positively to the Preventive Medicine Doctor training program from 2020 to 2023.
Keywords: feedback; curriculum; final year students; preventive medicine doctor